DAMPAK ISSUE BTS HIATUS TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY (TVA) TERHADAP PERUSAHAAN ENTERTAINMENT DI KOREA SELATAN - Alimi, Tanzila Azzalzal; Hadi, Abdul; Haris, Abdul (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2023)
This study aims to determine the impact of the Issue BTS Hiatus in entertainment company stock prices in South Korea which were published on June 14,2022. This study uses the event study method using indicators of abnormal return (AR) and trading volume activity (TVA) for the period before and after issue published. The population used is entertainment companies in South Korea which are listed on the Korea Stock Exchange and the sample technique is non probability sample of 15 companies is obtained. This analysis included descriptive analysis, normality test, hypothesis testing which was carried out using the paired sample t test for normally distributed data and the Wilcoxon signed rank test for abnormally distributed data. Using program SPSS version 22. The result of this study indicate that (1) there is a significant difference in the average abnormal return before and after the Issue BTS Hiatus is published, (2) there is a significant the average trading volume activity before and after the Issue BTS Hiatus is published. Keywords : Event Study, BTS Hiatus, Abnormal Return, Trading Volume Activity.